An Analysis of Qira’ah Textbooks for Islamic Senior Highschool: A Religious Moderation Perspective - Nasution, Sahkholid; Al-Rasyid, Harun; Wulandari, Putri; Khalila, Zikrani; Pasaribu, Baharuddin (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
Learning at Islamic schools functions to strengthen the values of religious moderation for students, so the selection of materials for all learning topics must support the transformation of religious moderation values, including in learning Arabic. This study aims to analyze the Arabic Maharah al-Qira’ah textbooks at Madrasa Aliyah (MA), which contain values of religious moderation. This study follows a qualitative-descriptive method. Data was collected using the content analysis method. The content analysis method is used to look at the constancy of the text content and the meaning of the contents of the Arabic Maharah al-Qira’ah textbooks at MA. The findings of this study indicate that the Arabic Qira’ah textbooks at MA contain religious moderation values including; national commitment, tolerance, anti-violence, and accommodation of local culture. The implications of this study are first, as an auto-corrective for Arabic textbook writers, and second, so that Arabic teachers can reinforce the values of religious moderation to students, both in the form of illustrations and by giving concrete examples in daily behavior.